The effect of transitioning from diesel to solar photovoltaic energy for irrigation tube wells on annual groundwater extraction in the lower Indus Basin, Pakistan - Muhammad Khalid Jamil; Wouter Julius Smolenaars; Bashir Ahmad; Sanita Dhaubanjar; Walter Willem Immerzeel; Arthur Lutz; Ghani Akbar; Fulco Ludwig; Hester Biemans (Journal of Agriculture and Food Research)
Nearly 86 % of the 1.4 million agricultural tube wells extracting groundwater for irrigation of crops in Lower Indus Basin (LIB) Pakistan are powered by diesel fuel. Diesel is expensive, needs to be imported and contributes to global warming through CO2 emissions. The increasing global focus on clean energy sources has prompted a shift from diesel fuel to solar photovoltaic (PV) energy for powering irrigation tube wells. The broad availability of inexpensive/free operational energy and abundant solar energy for pumping can cause over-extraction of groundwater. This study investigates the impacts of converting diesel pumps to solar PV pumps on groundwater extraction in LIB Pakistan. We conducted one-to-one comparisons of solar vs diesel pumps in thirty pairs of farmers working in similar circumstances. We estimated annual water extracted by solar and diesel pump farmers in each pair utilizing the data collected through flow measurements and crop wise irrigation times for each pair of farms using a targeted survey questionnaire, followed by a validation process. We utilized validated “Global Solar Atlas” (GSA), an online tool that accounts for daily and seasonal variation in solar pumps flows. Flow rates of diesel-operated pumps were measured, and annual water volumes pumped by both types of pumps were compared. Results show that the introduction of solar pumps significantly increased groundwater pumping compared to diesel fuelled pumps (P = 0.005∗). The average annual water pumped by solar and diesel pumps was found to be 1.6 ∗ 103 and 1.3 ∗ 103 mm respectively. In 77 % of the cases, farms using solar pumps extracted more water than their diesel counterparts under comparable conditions. While acknowledging benefits of solar PV pumping for agriculture in LIB Pakistan, the outcome of the study emphasized the need for a cautious and well-informed upscaling approach to avoid overextraction of groundwater.